Localizing matrix metalloproteinase activities in the pericellular environment. - Murphy, G; Nagase, H (2011)
Matrix metalloproteinases (MMPs) are a group of structurally related proteolytic enzymes containing a zinc ion in the active site. They are secreted from cells or bound to the plasma membrane and hydrolyze extracellular matrix (ECM) and cell surface-bound molecules. They therefore play key roles in morphogenesis, wound healing, tissue repair and remodeling in diseases such as cancer and arthritis. Although the cell anchored membrane-type MMPs (MT-MMPs) function pericellularly, the secreted MMPs have been considered to act within the ECM, away from the cells from which they are synthesized. However, recent studies have shown that secreted MMPs bind to specific cell surface receptors, membrane-anchored proteins or cell-associated ECM molecules and function pericellularly at focussed locations. This minireview describes examples of cell surface and pericellular partners of MMPs, as well as how they alter enzyme function and cellular behaviour.